Transport Costs and Prices of Transport Services ("Journal "U". Economy. Management. Finance.", 2020)
When we analyze the tasks that stem from the essence of logistics, we may conclude, among others, that logistics as such ensures the movement of goods to wherever there is a demand in its broad meaning; the recipient may be the consumer or other economic entity on micro and macro levels. One should remember, however that transport is executed by economic entities that realize objectives similar to those of production companies and their main task is the creation of added value (economic approach), which ensures the ongoing cash flow and the development of the company in the future.
Keywords: costs; cost; cost-effectiveness